Penggunaan Governing Languange Clause dan Translation Clause pada Perjanjian Berbahasa Asing - Velliana Tanaya; Harimurti Adi Nugroho (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
Since the enactment of Law No. 24/2009 on Flag, Language, National Emblems and the National Anthem (UU Bahasa), many court decisions arise related to the use of foreign languages (English) in agreements made between Indonesian Citizens or Indonesia Legal Entities with Foreigners or Foreign Legal Entities. One of the most well-known verdicts was the verdict that canceled the loan agreement between PT Bangun Karya Pertama Lestasri and Nine AM for violating Article 31 paragraph (1) UU Bahasa. This article discusses 4 cases that have been resolved by the State Court, the High Court and the Supreme Court where almost all of the decisions cancelled the agreements written in foreign languages. It is effected the businessman to use governing language clauses and translation clauses into foreign language agreements based on freedom of contract and pacta sunt servanda